(untitled) (Prilozi za orijentalnu filologiju, 2017)
Dr. K. Jireček in his well-known work Die Handelstrassen und Bergwerke Serbiens und Bosniens während des Mittelalters, Pragae, 1879, described, on the basis of the archival materials of the Dubrovnik Archives, in addition to the mines, the main lines of communication in Bosnia and Herzegovina in the period before the Turkish occupation. This new contribution represents in a way a continuation of Jireček's study and describes the lines of communication in the nex.t, Turkish period. The theme of the article is a description of a fairly large and characteristic area - the region of the former urban settlement of Rudo (near the present-day Rudo) on the Lim River (the Lower Lim Valley) in southeastern Bosnia. The article ds based primarily on the research carried out in the region itself and also on archival materials and other data. The research has shown that in the region in question there existed in the Turkish period and was used in entirety until 1878 (the Austro-Hungarian occupation) a large network of trade and travelers' lines of communication in. general. One road in this. Network served for inland and international traffic whereas the others were partly of regional, partly of local significance of inland significance was the road that led through this region, more precisely its eastern part, linking Višegrad with Sarajevo, Travnik, Banja Luka and the West on one side, and Priboj, Novi Pazar, Skoplje, Niš, Sofija, and Istanbul itself on the other, eastern side. This road was the most established trade and military line of communication through Bosnia towards the East. Many travelers and writers of travel accounts traveled by that road and left reports about it in their itineraries. In the network of other, regional and local roads in this region, the former urban settlement of Rudo characteristically stands out as a place with a key position. It used to be on the left bank of the Lim, opposite the present-day Rudo, but disappeared from the face of the earth in 1896 in the great flood of the Lim River. Rudo was thus linked by roads of regional category with Priboj, Višegrad, and even with Užice in Serbia on the eastern, and with Pljevlja, Čajniče, and Goražde on the other, western side. The road via Čajniče led further via Foča at the way to Dubrovnik the same can be said for the road via Pljevlja and so both these routes had partly an inland significance. Local roads linked Rudo with a large number of villages and hamlets of this region, because Rudo was their gravitational and economic center. The traffic network of the Lower Lim Valley was partly a heritage of the Middle Ages and was only further intensified in the Turkish period, and partly completely established in this latter time, especially as far as some regional and most local roads are concerned. A very favorable influence on the development of new lines of communication and the intensity of ·traffic on the existing and the new roads in this latter period was exerted by the growth of a number of economic points in the area, such as Višegrad, Priboj, Užice, Pljevlja, Čajniče, and Goražde, which had developed into important economic centers already tin the 16th century. There was, however, a converse influence also - the large network of lines of communication contributed to the development of these places as well. The most characteristic example in this latter respect is the urban settlement of Rudo itself, not only as regards the road network of this region but also of the whole of Bosnia and Herzegovina. This is because this settlement grow on the whole out of solely traffic reasons: the settlement was first founded in 1555 by .the then Bosnian sangak-bey Mustafabeg (later pasha) Sokolović, by birth from this region. In its statute, which established rules for life in the future settlement, it was literally said that in the Rudo Field there was a crossing (over the Lim River) and a land crossing (over the field), “Which are not for a single hour or at any time of day without those Who come and go, and, in addition, the region is far from any town (“šehir”) and thus there is a real necessity for building a bridge and founding a kasaba” (settlement of urban status) in that place.